Impermeable concrete and preparation method thereof
By using acrylate, acrylic acid and graphene oxide in anti-seepage concrete for organic and inorganic hybridization reactions, the composite hydrogel is formed, which solves the problem of insufficient strength of anti-seepage concrete and the inability to maintain graphene oxide for a long time, and achieves a concrete with high strength and excellent anti-seepage properties.
Patent Information
- Application Number
- CN202411965413.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
While improving the anti-seepage properties, the existing anti-seepage concrete has insufficient strength, and graphene oxide cannot be maintained in a high alkali environment for a long time, and cannot continue to exert waterproofing effect.
The organic and inorganic hybridization reaction is carried out by amine acrylic acid, acrylic acid and graphene oxide to form a composite hydrogel, improve the structure of cement hydrated slurry, improve the strength and impermeability of concrete, and protect graphene oxide through composite hydrogel, so that it can continue to play its role in a high alkali environment.
It improves the strength and permeability of concrete, reduces the shrinkage of concrete and repairs microcracks, extends the service life of concrete structures, and maintains the waterproof effect of graphene oxide in high alkali environments.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to an anti-seepage concrete and a preparation method thereof. Background Art
[0002] In order to obtain a certain plasticity and fluidity, the amount of water added to ordinary concrete should be much greater than its theoretical water requirement. Excess water escapes from the concrete, leaving pores in the concrete. The more water mixed, the more pores are formed. Therefore, in environments that require long-term immersion in water, such as underground building waterproofing, swimming pools, and cement depots, ordinary concrete has high water permeability, resulting in poor durability.
[0003] In the prior art, the anti-seepage performance of concrete is mainly improved by anti-seepage components. Currently, SAP can improve the anti-seepage of concrete and repair concrete cracks, but the strength of concrete is reduced. Even if concrete is reinforced with fibers, this is mainly through macro-toughening, and the concrete is not strengthened from the micro-mechanism of cement hydration. Although graphene oxide can improve the strength of concrete and improve anti-seepage, it cannot reduce shrinkage or repair concrete cracks.
[0004] Therefore, how to overcome the defect of insufficient strength of impermeable concrete caused by the impermeable components in the prior art is a technical problem that urgently needs to be solved in this field.
[0005] It should be noted that the above information disclosed in this background technology section is only used to understand the background technology of the present application concept, and therefore, the above description is not considered to constitute information of the prior art. Summary of the invention
[0006] The embodiments of the present disclosure at least provide an anti-seepage concrete and a preparation method thereof.
[0007] In a first aspect, an embodiment of the present disclosure provides an impermeable concrete, comprising the following components in parts by weight: 220-280 parts of cement, 40-70 parts of fly ash, 50-100 parts of mineral powder, 0.3-2 parts of a densifier, 6-8 parts of a water reducer, 650-850 parts of sand, and 900-1100 parts of gravel; wherein the densifier comprises acrylamide, acrylic acid, and graphene oxide.
[0008] In an optional embodiment, the preparation method of the densifier includes the following steps: step S1, heating graphene oxide, acrylamine, acrylic acid and methylene acrylamide in a water bath to 50-55°C under an inert gas atmosphere, and stirring for 1-2 hours to obtain a mixture; step S2, adding ammonium persulfate and tetramethylethylenediamine to the mixture, stirring until completely dissolved, and treating with water for 18-24 hours to obtain a gel product; step S3, drying the gel product at 105-110°C, and crushing it to obtain a densifier.
[0009] In an optional embodiment, the particle size of the densifying agent is less than 100 μm.
[0010] In an alternative embodiment, the cement comprises ordinary silicate P.II52.5.
[0011] In an optional embodiment, the fly ash includes primary fly ash.
[0012] In an optional embodiment, the mineral powder includes S95 grade mineral powder.
[0013] In an optional embodiment, the sand is machine-made sand with a fineness modulus of 2.5-3.0.
[0014] In an optional embodiment, the stones are crushed stones with a particle size of 5-25 mm.
[0015] In a second aspect, the embodiments of the present disclosure also provide a method for preparing the impermeable concrete as described above, comprising the following steps: step S1, respectively mixing cement, fly ash, mineral powder, compacting agent, sand, gravel and water to obtain a premix; step S2, adding a water reducer to the concrete mixing water and mixing evenly, and adding it to the premix, stirring thoroughly for 5-10 minutes, to obtain precast concrete; step S3, pouring the precast concrete into a mold, and curing to obtain the impermeable concrete.
[0016] In an optional embodiment, the curing time in step S3 is not less than 28 days.
[0017] The beneficial effect of the present invention is that the anti-seepage concrete and its preparation method form a composite hydrogel through an organic-inorganic hybrid reaction of acrylamide, acrylic acid and graphene oxide, so as to improve the cement hydration slurry structure, increase the strength of concrete, reduce concrete shrinkage and repair concrete microcracks, thereby improving the waterproof and anti-seepage performance of concrete throughout the whole process. In addition, the composite hydrogel environment also provides protection for graphene oxide, so that it can continue to exert its effect in the high-alkali environment of concrete.
[0018] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description.
[0019] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below for detailed description as follows. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] As used herein, the phrases "in one embodiment," "according to one embodiment," "in some embodiments," and the like generally refer to the fact that the particular feature, structure, or characteristic following the phrase may be included in at least one embodiment of the present disclosure. Therefore, a particular feature, structure, or characteristic may be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example," "exemplary," and the like are used to "serve as an example, instance, or illustration." Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. On the contrary, the use of the terms "example," "exemplary," and the like is intended to present concepts in a concrete manner.
[0022] In this document, as used herein, expressions such as "at least one of..." when following a list of elements modify the entire list of elements rather than modifying the individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.
[0023] The terms used herein are only used to describe specific exemplary configurations and are not intended to be limited. As used herein, the singular articles "one", "an" and "the" may also be intended to include plural forms, unless it is clearly indicated above that this is not the case. The terms "comprise", "include" and "have" are inclusive, and therefore specify the presence of features, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless specifically identified as an execution order. Additional or alternative steps may be adopted.
[0024] For impermeable concrete, the following technical solutions are available:
[0025] (1) A high-strength impermeable concrete and its preparation method (licensing announcement number CN 116003045 B) uses a certain proportion of nano-silicon dioxide, nano-graphene, coconut shell powder, and sodium lignin sulfonate as a modified admixture to form a better spatial network structure, which is more conducive to improving the concrete's impermeability and strength. Moreover, combined with calcium sulfoaluminate-calcium oxide expansion agents, it is more conducive to the formation of spatial structures and further improves the performance of concrete.
[0026] (2) A kind of impermeable concrete and its preparation method (application publication number CN 117326835 A), wherein basalt fiber is put into dimethyl sulfoxide, polyacrylamide is added and stirred, ammonium persulfate and N,N-methylenebisacrylamide are added and stirred to react, the liquid is filtered out and then dried at a constant temperature to obtain polyacrylamide-modified basalt fiber to improve the impermeability of concrete.
[0027] (3) A kind of impermeable concrete and its preparation method (authorization announcement number CN 118184248 B) By adding SAP and polypropylene fibers to concrete and designing a certain mix ratio, the impermeability performance is improved while ensuring the strength of concrete, the penetration of water is reduced, and the service life of the concrete structure is extended.
[0028] (4) An environmentally responsive polymer self-repairing mortar and its preparation (authorization announcement number CN 112710519B) in which the water-absorbing polymer structure is ionized and modified so that its performance as a concrete self-repairing agent and its repair performance can meet actual use requirements.
[0029] (5) An impermeable concrete and its preparation method (application publication number CN 117486578 A) The impermeable concrete includes an impermeable component, and the impermeable component also includes a super absorbent resin. The waterproofing agent is added to the cement. The super absorbent resin absorbs water and expands, and has a water-locking function, which resists the shrinkage of the concrete during the pouring and hardening process, avoids the shrinkage and cracking of the concrete, improves the impermeability of the concrete, and improves its waterproof and anti-seepage effect.
[0030] In the prior art, the anti-seepage performance of concrete is mainly improved by anti-seepage components. At present, SAP can improve the anti-seepage of concrete and repair concrete cracks (authorization announcement number CN 118184248 B, authorization announcement number CN 112710519B, application publication number CN 117486578A), but the strength of concrete is reduced. Even if the concrete is reinforced with fibers, this is mainly through macro-toughening (application publication number CN 117326835A, authorization announcement number CN 118184248 B), but the concrete is not strengthened from the microscopic mechanism of cement hydration. Although graphene oxide can improve the strength of concrete (authorization announcement number CN116003045 B) and improve anti-seepage, it cannot reduce shrinkage and repair concrete cracks.
[0031] The defects existing in the above solutions are the results obtained by the inventor after practice and careful research. Therefore, the discovery process of the above problems and the solutions proposed by the present disclosure for the above problems below should be the contributions made by the inventor to the present disclosure during the disclosure process.
[0032] Some embodiments of the present invention are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0033] An embodiment of the present disclosure provides an impermeable concrete, comprising the following components in parts by weight: 220-280 parts of cement, 40-70 parts of fly ash, 50-100 parts of mineral powder, 0.3-2 parts of a densifier, 6-8 parts of a water reducer, 650-850 parts of sand, and 900-1100 parts of gravel; wherein the densifier comprises acrylamide, acrylic acid, and graphene oxide.
[0034] In some embodiments, specifically, the preparation method of the densifier includes the following steps: step S1, heating graphene oxide, acrylamine, acrylic acid and methylene acrylamide in a water bath under an inert gas atmosphere to 50-55°C, keeping warm and stirring for 1-2 hours to obtain a mixture; step S2, adding ammonium persulfate and tetramethylethylenediamine to the mixture, stirring until completely dissolved, and treating with water for 18-24 hours to obtain a gel product; step S3, drying the gel product at 105-110°C, and crushing to obtain a densifier.
[0035] Specifically, graphene oxide cannot be maintained for a long time in the strong alkaline environment of concrete. After being synthesized into a gel-like product, it can protect the graphene oxide and thus exert its effect in concrete.
[0036] In some embodiments, specifically, the particle size of the densifying agent is less than 100 μm.
[0037] In some embodiments, specifically, the cement comprises ordinary silicate P.II52.5.
[0038] In some embodiments, specifically, the fly ash includes primary fly ash.
[0039] In some embodiments, specifically, the mineral powder includes S95 grade mineral powder.
[0040] In some embodiments, specifically, the sand is machine-made sand with a fineness modulus of 2.5-3.0, preferably machine-made sand with a fineness modulus of 2.8.
[0041] In some embodiments, specifically, the stones are crushed stones with a particle size of 5-25 mm.
[0042] The embodiment of the present disclosure also provides a method for preparing the impermeable concrete as described above, comprising the following steps: step S1, respectively mixing cement, fly ash, mineral powder, compacting agent, sand, gravel and water to obtain a premix; step S2, adding a water reducer to concrete mixing water and mixing evenly, and adding the water reducer to the premix, stirring thoroughly for 5-10 minutes, to obtain precast concrete; step S3, pouring the precast concrete into a mold, and curing to obtain the impermeable concrete.
[0043] Embodiment 1:
[0044] (1) This embodiment provides a method for preparing an anti-seepage concrete densifier component, specifically,
[0045] First, graphene oxide, acrylic amine, acrylic acid and methylenebisacrylamide were weighed in a mass ratio of 2.5:10:15:0.5, heated in a water bath to 50°C-55°C for 2h under a nitrogen atmosphere, and ammonium persulfate and tetramethylethylenediamine were added during the stirring process, the ratio of tetramethylethylenediamine to ammonium persulfate was 0.5:0.2, and after the stirring was completed, the hydrogel was treated for 24h to obtain the hydrogel. The obtained gel product was dried at 105°C and crushed to obtain the densifier with particles less than 100μm.
[0046] (2) Materials used in this mix ratio: 240 parts of cement, 60 parts of fly ash, 80 parts of mineral powder, 0.76 parts of densifier, 5 parts of water reducer, 700 parts of sand, 1100 parts of gravel, and 160 parts of water. Add them to the concrete mixer in sequence and mix them evenly. At the same time, add the water reducer to the concrete mixing water and mix them evenly. Then add the water and water reducer mixed liquid to the concrete mixer, stir them thoroughly for 5 to 10 minutes, take them out, pour them into the mold, and cure them for 28 days to obtain impermeable concrete.
[0047] Embodiment 2:
[0048] (1) The difference from Example 1 is that the amount of densifier added is different.
[0049] The preparation method of the compacting agent is as shown in Example 1.
[0050] (2) Materials used in this mix ratio: 240 parts of cement, 60 parts of fly ash, 80 parts of mineral powder, 1.52 parts of densifier, 5 parts of water reducer, 700 parts of sand, 1100 parts of gravel, and 152 parts of water. Add them to the concrete mixer in sequence and mix them evenly. At the same time, add the water reducer to the concrete mixing water and mix them evenly. Then add the water and water reducer mixed liquid to the concrete mixer, stir them thoroughly for 5 to 10 minutes, take them out, pour them into the mold, and cure them for 28 days to obtain impermeable concrete.
[0051] Embodiment 3:
[0052] (1) The difference from Example 1 is that the density agent ratio is different.
[0053] First, graphene oxide, acrylic amine, acrylic acid and methylenebisacrylamide were weighed in a mass ratio of 5:10:15:0.5, heated in a water bath to 50°C-55°C for 2h under a nitrogen atmosphere, and ammonium persulfate and tetramethylethylenediamine were added during the stirring process, the ratio of tetramethylethylenediamine to ammonium persulfate was 0.5:0.2, and after the stirring was completed, the hydrogel was treated for 24h to obtain the hydrogel. The obtained gel product was dried at 105°C and crushed to obtain the densifier with particles less than 100μm.
[0054] (2) Referring to the mix proportion and preparation method of Example 1, the densifier of step (1) is added to obtain the target concrete.
[0055] Embodiment 4:
[0056] (1) The difference from Example 1 is that the density agent ratio is different.
[0057] First, graphene oxide, acrylic amine, acrylic acid and methylenebisacrylamide were weighed in a mass ratio of 1:10:15:0.5, heated in a water bath to 50°C-55°C for 2h under a nitrogen atmosphere, and ammonium persulfate and tetramethylethylenediamine were added during the stirring process, the ratio of tetramethylethylenediamine to ammonium persulfate was 0.5:0.2, and after the stirring was completed, the hydrogel was treated for 24h to obtain the hydrogel. The obtained gel product was dried at 105°C and crushed to obtain the densifier with particles less than 100μm.
[0058] (2) Referring to the mix proportion and preparation method of Example 1, the densifier of step (1) is added to obtain the target concrete.
[0059] The concrete obtained in the above examples 1-4 was tested for impermeability and strength according to national standards, wherein the concrete impermeability was tested by water penetration resistance test according to GB / T / 50082-2009 standard, and the results are shown in Table 1 below:
[0060] Table 1 Impermeability and strength of concrete prepared in Examples 1-4
[0061] Impermeability grade Strength (MPa) Example 1 >P14 52.3 Example 2 >P14 57.8 Example 3 >P14 54.6 Example 4 >P12 50.7
[0062] Specifically, Examples 1-3 provided by the present invention all exhibit excellent anti-seepage effects and strengths, but Example 4 has a low anti-seepage grade because the amount of graphene oxide added is too low and cannot provide sufficient waterproofing effects.
[0063] In summary, the anti-seepage concrete and its preparation method form a composite hydrogel through an organic-inorganic hybrid reaction of acrylamide, acrylic acid and graphene oxide, so as to improve the cement hydration slurry structure, increase the strength of concrete, reduce concrete shrinkage and repair concrete microcracks, thereby improving the waterproof and anti-seepage performance of concrete throughout the whole process. In addition, the composite hydrogel environment also provides protection for graphene oxide, enabling it to continue to exert its effect in the high-alkaline environment of concrete.
[0064] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. An impermeable concrete, characterized in that: The composition comprises the following components in parts by weight: 220-280 parts of cement, 40-70 parts of fly ash, 50-100 parts of mineral powder, 0.3-2 parts of compacting agent, 6-8 parts of water reducing agent, 650-850 parts of sand, 900-1100 parts of gravel; The compacting agent comprises acrylic amine, acrylic acid and graphene oxide.
2. The impermeable concrete according to claim 1, characterized in that: The preparation method of the compacting agent comprises the following steps: Step S1, heating graphene oxide, acrylamine, acrylic acid and methylene acrylamide in a water bath to 50-55° C. under an inert gas atmosphere, and stirring for 1-2 hours to obtain a mixture; Step S2, adding ammonium persulfate and tetramethylethylenediamine to the mixture, stirring until completely dissolved, and treating with water for 18-24 hours to obtain a gel product; Step S3, drying the gel product at 105-110° C. and crushing it to obtain a densifier.
3. The impermeable concrete according to claim 2, characterized in that: The particle size of the compacting agent is less than 100 μm.
4. The impermeable concrete according to claim 1, characterized in that: The cement comprises ordinary silicate P.II52.
5.
5. The impermeable concrete according to claim 1, characterized in that: The fly ash includes primary fly ash.
6. The impermeable concrete according to claim 1, characterized in that: The mineral powder includes S95 grade mineral powder.
7. The impermeable concrete according to claim 1, characterized in that: The sand is machine-made sand with a fineness modulus of 2.5-3.
0.
8. The impermeable concrete according to claim 1, characterized in that: The stones are crushed stones with a particle size of 5-25 mm.
9. A method for preparing the impermeable concrete according to any one of claims 1 to 8, characterized in that: The steps include: Step S1, respectively mixing cement, fly ash, mineral powder, compacting agent, sand, gravel and water to obtain a premix; Step S2, adding the water reducing agent to the concrete mixing water and mixing evenly, and adding it to the premix, stirring thoroughly for 5-10 minutes to obtain precast concrete; Step S3, pouring the precast concrete into a mold and curing to obtain impermeable concrete.
10. The preparation method according to claim 9, characterized in that: The curing time in step S3 is not less than 28 days.
Citation Information
Patent Citations
An environmentally responsive polymer self-healing mortar and its preparation method
CN112710519B
High-strength impermeable concrete and preparation method thereof
CN116003045B
Impermeable concrete and preparation method thereof
CN117326835A
Impermeable concrete and preparation method thereof
CN117486578A
A kind of impermeable concrete and preparation method thereof
CN118184248B